Internet Marketing: Solusi Bagi Pengusaha Bermodal Kecil - Cahyadi, A. (Bina Nusantara University, 2005)
Marketing is an integral part of any businesses who based its existence on profit. In its history marketing strategy has evolved several times into a strategy focusing more and more towards consumers needs. One of the marketing strategies that is currently being highlighted is Internet Marketing. This article tries to identify the advantage and weaknesses of Internet marketing and based on this fact recommends the most approriate internet promotion tools for e-enteprenuers with limited budget. At the end, article expresses some possibilities on Internet marketing adoption by Small and Medium Scale Enteprenuers in Indonesia.